Multicomponent Reactions of Pyridines To Give Ring‐Fused Pyridiniums: In Situ Activation Strategy Using 1, 2‐Dichloroethane as a Vinyl Equivalent. Issue 1 (30th November 2018) - Wang, Zhishuo; Yin, Jiangliang; Zhou, Fulin; Liu, Yunqi; You, Jingsong
Abstract: Reported herein is a rhodium(III)‐catalyzed three‐component annulation reaction of simple pyridines, alkynes, and 1, 2‐dichloroethane (DCE), affording a streamlined pathway to diverse ring‐fused pyridiniums. DCE not only serves as a vinyl equivalent but also as an in situ activating agent for pyridine C2−H activation. A cationic five‐membered rhodacycle complex has been isolated and proposed as a possible intermediate. This strategy can be extended to other N‐containing heteroarenes for the synthesis of multiring‐fused pyridiniums. These multicomponent reactions exhibit excellent regioselectivity for 1, 3‐diynes, paving a path to the cascade cyclization of 3‐fluoropyridine or N ‐methylpyridin‐3‐amine with 1, 3‐diynes for the construction of brand‐new tricyclic‐fused pyrano‐ or hydropyridoquinolizinium salts. These ionic fluorophores have been investigated as potential biomarkers. Abstract : Triple agent : Disclosed herein is a rhodium(III)‐catalyzed multicomponent reaction of simple pyridines, alkynes, and 1, 2‐dichloroethane (DCE) to afford a streamlined pathway to diverse ring‐fused pyridiniums. DCE serves as a vinyl equivalent and an in situ activating agent for pyridine C2−H activation, as well as a solvent.